2017
DOI: 10.1371/journal.pone.0181842
|View full text |Cite
|
Sign up to set email alerts
|

Targeted next-generation sequencing detects novel gene–phenotype associations and expands the mutational spectrum in cardiomyopathies

Abstract: Cardiomyopathies are a heterogeneous group of primary diseases of the myocardium, including hypertrophic cardiomyopathy (HCM), dilated cardiomyopathy (DCM), and arrhythmogenic right ventricular cardiomyopathy (ARVC), with higher morbidity and mortality. These diseases are genetically diverse and associated with rare mutations in a large number of genes, many of which overlap among the phenotypes. To better investigate the genetic overlap between these three phenotypes and to identify new genotype–phenotype cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 88 publications
(111 reference statements)
1
27
0
1
Order By: Relevance
“…The patient in our study, a Chinese national clinically diagnosed with ARVC according to the criteria set by the Task Force 24 , developed this novel heterozygous mutation in OBSCN that might be of relevance to the pathogenesis of ARVC (whole genome sequencing did not detect other genes known to be associated with ARVC). The T-wave inversion and epsilon waves clinically manifested in the electrocardiogram and the right ventricular abnormality on the echocardiography observed in our patient were similar to the Italian-based clinical characteristics portrayed in patients with ARVC also carrying mutations in OBSCN 21 , 23 . We also determined that the OBSCN mutation was related to the decrease of protein expression level of obscurin, pointing to haploinsufficiency as a possible disease-causing mechanism.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The patient in our study, a Chinese national clinically diagnosed with ARVC according to the criteria set by the Task Force 24 , developed this novel heterozygous mutation in OBSCN that might be of relevance to the pathogenesis of ARVC (whole genome sequencing did not detect other genes known to be associated with ARVC). The T-wave inversion and epsilon waves clinically manifested in the electrocardiogram and the right ventricular abnormality on the echocardiography observed in our patient were similar to the Italian-based clinical characteristics portrayed in patients with ARVC also carrying mutations in OBSCN 21 , 23 . We also determined that the OBSCN mutation was related to the decrease of protein expression level of obscurin, pointing to haploinsufficiency as a possible disease-causing mechanism.…”
Section: Discussionsupporting
confidence: 85%
“…In a study of 30 index patients with end-stage heart failure, mutations in OBSCN were identified in 5 subjects (17%) 21 . similarly, heterozygous mutations in OBSCN were identified in 6 of 74 unrelated individuals with hypertrophic cardiomyopathy, and in 3 of 10 patients with left ventricular densification 23 .…”
Section: Discussionmentioning
confidence: 87%
“…Although this report found no connections of coexisting trabeculations that fit within NC/C ratio criteria in DCM with clinical points, it only could be partially compared to the present study and our previous study due to using triple criteria of thinning of the compact myocardium, NC/C ratio, and sufficient share of non-compact myocardium in total mass of the left ventricle [ 27 ]. The second most common combination, DCM/HCM, was found in nearly one-third of our overlapping patients, but this combination could be even more powerfully connected with undesirable prognosis due to partially shared gene basics [ 28 , 29 ]. The least frequent combination in our settings was the DCM/HCM/LVNC, with only a single case in the monitored period, which was also previously described in a large registry with clinical endpoints, which reported a greater incidence of cardiovascular adverse events [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…47,5052 Recent research encompassing other genes having sporadic PMs identified several rare variants underlying both HCM and DCM. 53 Seeing how pleiotropic PMs of sarcomeric genes can elicit such strikingly contrasting (Figures 2–4) phenotypes as HCM and DCM has spurred sarcomere-biology research, 54 and the sarcomere’s chemomechanical cross-bridge kinetics/dynamics cycle clarified how cardiomyopathic PMs perturb force-production. 55 Briefly, myosins consist of a head motor-domain (MD), which generates movement, and a neck (lever-arm) transitioning into the tail domain and associated with several regulatory light-chain subunits (cf.…”
Section: From Gene-variants To Cm-phenotypesmentioning
confidence: 99%